Assessment of Quality of Life in Cancer Patients Undergoing Chemotherapy Treatment Using EORTC QLQ-C30 Questionnaire - Samah E. EL-Najjar; Ihab A. Naser; Kanan M. AL-Wahidi (Proceedings)
Cancer is a challenge for the majority of the population’s health-related quality of life (HRQoL), compromising their physical health and emotional well-being. This study aimed to assess the QoL, differentiate QoL among different groups, and explore its association with other factors in adult cancer patients undergoing chemotherapy treatment. All adult newly diagnosed cancer patients from the Oncology Department at the European Gaza Hospital (EGH) were eligible for participation in an ongoing prospective short cohort study. The European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core30 (EORTC QLQ-C30 was used to assess QoL in cancer patients after the completion of the chemotherapy regimen. A simple, self-administered assessment tool, Patient Neurotoxicity Questionnaire (PNQ) which is increasingly used in clinical praxis with significantly positive results has been used. The mean age of patients was 48.58 years. The global health status and functional scales, in most domains, were low, while the symptoms scales were moderate-to-high for most items, showing worse QoL. Fatigue and pain were the most disturbing symptoms. Global health and social functioning were better in over-weight and obese patients (p < 0.05). Malnourished patients and patients at risk of malnutrition showed a worse level of global health status in comparison to well-nourished patients (p = 0.049). Cancer stage significantly affects QoL (p < 0.05). The correlation of functional scales with global health status was found higher; the Spearman correlation r > 0.30 and showed a significant positive relationship (p < 0.05). Patients with a high PNQ score (more severe chemotherapy-induced peripheral neuropathy (CIPN) symptoms) reported a worse global quality of life and worse physical, work, emotional, cognitive, and social functioning compared with those with a low PNQ score. Cancer patients had a worse QoL regarding overall global health status as well as functional and symptom scales. CIPN is associated with HRQoL in cancer patients. Future studies should focus on understanding the mechanisms underlying CIPN so targeted interventions can be developed to reduce the impact of CIPN on patients’ lives.